Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper analyzes the main factors underlying the evolution of competitiveness, export performance, and labor market developments in Poland. The paper seeks to identify key questions of relevance for policymaking. The overall evolution of competitiveness compared with Poland's trading partners and competitors since 1995 is analyzed using standard measures of the real effective exchange rate (REER). This paper also examines the role of foreign investors in financing domestically issued public debt in Poland.